Effect of Fusarium graminearum phytotoxins on germinating seeds and tissue of wheat in relation to Fusarium head blight resistance - and A. ALIZADEH, B.S. PAKDAMAN, E. MOHAMMADI GOLTAPEH* (Indian Phytopathology, 2006)
Twenty six spring lines of bread wheat (Triticum aestivum L.) were studied from the view point of their tolerance to phytotoxins of Fusarium head blight caused by Fusarium graminearum Schwabe; the correlation between their tolerance to phytotoxic extract and field resistance were studied using semi-purified phytotoxins on growing coleoptiles segments. The results showed that although there was a great variability among different wheat lines regarding their tolerance to semi-purified phytotoxins, there were no correlations between tolerance of semi-purified phytotoxins and disease index (R=O.Oa"S), and between their tolerance and disease incidence (R = -0.08ns).